2014
DOI: 10.1016/j.bpj.2014.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Histones and DNA Compete for Binding Polyphosphoinositides in Bilayers

Abstract: Recent discoveries on the presence and location of phosphoinositides in the eukaryotic cell nucleoplasm and nuclear membrane prompted us to study the putative interaction of chromatin components with these lipids in model membranes (liposomes). Turbidimetric studies revealed that a variety of histones and histone combinations (H1, H2AH2B, H3H4, octamers) caused a dose-dependent aggregation of phosphatidylcholine vesicles (large unilamellar vesicle or small unilamellar vesicle) containing negatively charged pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Positively charged histones preferentially bind anionic phospholipids such as cardiolipin or phosphatidylserine, but not zwitterionic phospholipids like phosphatidylcholine 132. Furthermore, adding negative charge (eg, a phosphate head group as in phosphatidylinositol bis‐phosphate) increases the binding capacity of histones as measured by calorimetry 128. Histones have also been shown to expose phosphatidylserine on the surface of red blood cells in a dose‐dependent manner47; however, it is unclear whether this is as a result of altering flippase kinetics or via induction of apoptosis pathways.…”
Section: Molecular Basis Of Histone‐related Cellular and Tissue Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Positively charged histones preferentially bind anionic phospholipids such as cardiolipin or phosphatidylserine, but not zwitterionic phospholipids like phosphatidylcholine 132. Furthermore, adding negative charge (eg, a phosphate head group as in phosphatidylinositol bis‐phosphate) increases the binding capacity of histones as measured by calorimetry 128. Histones have also been shown to expose phosphatidylserine on the surface of red blood cells in a dose‐dependent manner47; however, it is unclear whether this is as a result of altering flippase kinetics or via induction of apoptosis pathways.…”
Section: Molecular Basis Of Histone‐related Cellular and Tissue Injurymentioning
confidence: 99%
“…Once integrated, histones induce permeabilization of membranes to cations, disruptions of cellular calcium signalling112 and cell death by necrosis. Negatively charged acute‐phase proteins (such as C‐reactive protein, CRP),14 DNA,128 innate polysaccharides (heparin)120 or synthetic macromolecules126 compete with membrane phospholipids and prevent histone integration and toxicity. Bactericidal properties of histone fragments are dependent on their ability to form amphipathic α‐helices—potentially membrane spanning domains—however no such structural analyses have been performed on mammalian cells to date 89…”
Section: Molecular Basis Of Histone‐related Cellular and Tissue Injurymentioning
confidence: 99%
“…1, 2, 3, 4, and 5) demonstrate that histones cause effects that in combination are diagnostic for membrane fusion. In our previous study (13), we showed that PIP could compete with DNA for histones. Together, our previous and current data suggest a complex multiple equilibrium in which free and bound DNA, free and bound histones (specifically H1) (44) and membranes, and nonfused and fused vesicles may coexist in the close vicinity of the nucleoplasmic reticulum.…”
Section: Vesicle-vesicle Fusionmentioning
confidence: 98%
“…Isothermal calorimetry data for the lipidprotein interaction were compatible with phosphoinositide/ histone stoichiometries of~0.5 (PIP) and~1.0 (PI), respectively. Moreover, competition experiments involving histones and negatively charged vesicles and DNA demonstrated the possibility of coexisting DNA-and PIP-bound histones (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation